Phylogenetic relationships and evolution of the musculoskeletal system of Polynemidae (Teleostei: Percomorphacea: Perciformes - Migliavacca, Paulo Presti (2019)
Polynemidae is a family of primarily marine fishes with eight genera and 42 extant species. The phylogenetic allocation of polynemids within Percomorphacea as well as its internal relationships are uncertain as highly conflicting hypotheses has been proposed in the literature. Many aspects of the polynemid morphology are largely unknown, with little reports in the literature about their osteology, barely any information on their myology, and no studies on the ontogeny of their skeleton. This project aimed to study different aspects of the musculoskeletal system of Polynemidae and understand its internal relationships. The most remarkable feature of polynemids is their pectoral fin divided into an upper, unmodified fin and a lower portion with rays highly modified into specialized filaments. The present analysis reveals that the main adductor and abductor muscles masses of the pectoral fin involved in such intricate structure are completely divided into two muscle segments that serve separately the pectoral-fin rays, dorsally, and pectoral filaments, ventrally. Interestingly, it is herein demonstrated that the pectoral filaments receive massive nerves specialized in gustatory reception, indicating that the polynemid pectoral filament have not only tactile but also tasting functions. Several unique specializations in the mandibular, hyopalatine and branchial musculature of polynemids are herein reported for the first time. A comprehensive cladistic analysis based on 162 morphological characters and all valid polynemid genera was performed and resulted in fully resolved new hypothesis of relationships. All genera were recovered as monophyletic except Polydactylus, which is polyphyletic. Lastly, a survey of the skeletogenesis of polynemids reveals remarkable changes during their ontogeny, such as the shifting in pectoral radial 3 and the expansion of pectoral radial 4, both transformations associated with the differentiation of the pectoral filaments. The saddle-like ossification pattern of vertebral centra 1-4 of polynemids is only shared with sciaenids and additionally supports the hypothesis of a closer relationship between these families.